Принципи формування окремої криміналістичної методики - Степанюк, Р. Л.; Stepaniuk, R. L.; ORCID: http://orcid.org/0000-0002-8201-4013 (Право і безпека. – 2016. – № 4 (63). – С. 85–90, 2016)
Розглянуто основні наукові підходи до системи принципів побудови криміналістичної методики розслідування окремих видів злочинів. Здійснено критичний аналіз запропонованих у спеціальній літературі основоположних правил цього напряму науково-дослідної діяльності, запропоновано авторське бачення щодо цього питання. Зокрема, визначено принципи правової основи, наукової основи та практичної основи як головні засади створення окремої криміналістичної методики.

The author has considered the main scientific approaches to the system of principles of constructing criminalistics technique of investigating certain types of crimes. The author has carried out a critical analysis of the basic rules of this direction of research activities offered in special literature. The necessity of a clear differentiation of general principles of scientific search and specific rules of construction of particular forensic techniques has been outlined. The author has offered his own vision on this issue. In particular, the author has defined the principles of the legal basis, scientific and practical basis as the main sources of forming particular forensic technique. Herewith the principle of legal basis means obligatory accounting the requirements of regulatory acts related to the developed scientific product. The scientific basis provides the knowledge and use of the latest achievements of criminalistics and other sciences, the provisions of which are needed to build the appropriate technique, as well as compliance with the general rules of research in the process of its formation. In its turn, information and practical basis means obligatory deep studying by a researcher of criminal activities of a certain type, features in detecting and investigation of the variety of crimes, their prevention, as well as the account of the needs and opportunities of operative and search, investigative, expert and judicial practice.

Рассмотрены основные научные подходы к системе принципов построения криминалистической методики расследования отдельных видов преступлений. Осуществлён критический анализ предложенных в специальной литературе основных правил данного направления научно-исследовательской деятельности, предложено авторское видение по данному вопросу. В частности, определены принципы правовой основы, научной основы и практической основы как главные начала создания частной криминалистической методики.
Principles of forming of a particular criminalistics technique
Принципы формирования частной криминалистической методики
Степанюк, Р. Л. Принципи формування окремої криміналістичної методики / Р. Л. Степанюк // Право і безпека. – 2016. – № 4 (63). – С. 85–90.
Степанюк Р. Л. "Принципи формування окремої криміналістичної методики." Право і Безпека 4 (2016): 85-90.
Stepaniuk, R.L. (2016), “Principles of forming of a particular criminalistics technique” [“Pryntsypy formuvannia okremoi kryminalistychnoi metodyky”], Pravo i Bezpeka, No. 4, pp. 85–90.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; криміналістична методика; досудове розслідування; принципи криміналістичної методики; criminalistics; forensic techniques; pre-trial investigation; formation of investigative techniques; principles of criminalistics techniques; криминалистическая методика; досудебное расследование; принципы криминалистической методики; Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право